If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + -8a + -1 = 10 Reorder the terms: -1 + 9a + -8a = 10 Combine like terms: 9a + -8a = 1a -1 + 1a = 10 Solving -1 + 1a = 10 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 1a = 10 + 1 Combine like terms: -1 + 1 = 0 0 + 1a = 10 + 1 1a = 10 + 1 Combine like terms: 10 + 1 = 11 1a = 11 Divide each side by '1'. a = 11 Simplifying a = 11
| 6[(x/15)-(1/2)=(2x=5)/6] | | 40+3x=5x | | 15=7+6 | | x-3=2x-56 | | 5/4x10 | | 12-1(x+1)=4 | | cos^4x-1=0 | | 11-h=8 | | x/15-5=6 | | =-6/0 | | x+41=x+12 | | 6b(6b+8)= | | 14=13-u | | 6x^2+6=12 | | x+136=180 | | -2p-15p=17 | | 16y^3=25x | | 2/5(45) | | 9/r=3 | | 2/5x-3/43 | | 11x=17x-30 | | (3+7i)+(4-3i)= | | 6r+9= | | -35+5= | | 5s+2s=7 | | 2A=41-A | | 2(r-3)=8 | | 2(e-3)=8 | | 3n+7=9n+21 | | 5.5+(-6.9)= | | 6y(3yx+5X)+2w=1 | | x/6=-22/33 |